Compound Taxus chinensis Capsule Combined with Chemotherapy for Non-Small-Cell Lung Cancer: A PRISMA-Compliant Systematic Review and Meta-Analysis of Randomized Controlled Trials. (16th December 2021) - Li, Keshuai; Cheng, Haibo; Shen, Weixing; Leung, Elaine Lai-Han; Le, Shao; Yu, Lili; Xie, Han; Sui, Xinbing; Zhu, Xiaoming; Wu, Qibiao
Abstract : Background . Compound Taxus chinensis capsule (CTCC), an antitumor Chinese patent medicine, has been commonly prescribed as an adjunctive agent to chemotherapy for the management of non-small-cell lung cancer (NSCLC); however, the effects of CTCC added to chemotherapy for NSCLC patients have never been comprehensively evaluated or summarized. Purpose . To assess the synergistic effects of CTCC and chemotherapy on NSCLC. Study Design . Evidence-based study, systematic review, and quantitative meta-analysis. Methods . This systematic review and meta-analysis was implemented in accordance with the PRISMA (Preferred Reported Items for Systematic Review and Meta-Analysis) guidelines. Eight databases including China National Knowledge Infrastructure, SINOMED, China Biomedical Literature Database, Wanfang Database, VIP, PubMed, Cochrane Library, and EMBASE were searched for relevant RCTs from their inception until May 24, 2021, and hand-searching was also carried out to identify additional studies. All randomized controlled trials (RCTs) that compared CTCC combined with chemotherapy versus chemotherapy alone were included in our study. The Cochrane Risk-of-Bias tool was used to determine the risk of bias and methodological quality of the included RCTs. Review Manager 5.3 software was used for comprehensive analysis. The primary outcome measure for this study was the disease control rate (DCR), and the secondary outcomes included the objective response rate (ORR), adverse reactions, and quality of life (QOL). Results. Six RCTs with a total sample size of 410 were finally included. The pooled data showed that, compared with chemotherapy alone, CTCC combined with chemotherapy significantly improved DCR (RR = 1.15, 95% CI: 1.06–1.25, P = 0.006), ORR (RR = 1.38, 95% CI: 1.18–1.63, P < 0.00001), and QOL (MD = 8.69, 95% CI: 7.26–10.13, P < 0.006) and reduced the incidence of total adverse reactions (RR = 0.48, 95% CI: 0.38–0.60, P < 0.00001). The subgroup analyses indicated that CTCC plus chemotherapy significantly improved gastrointestinal reactions (P = 0.004), leukopenia (P = 0.0009), thrombocytopenia (P = 0.01), rash (P = 0.002), and fever (P = 0.007). Conclusion . Based on the available evidence, compared with chemotherapy alone, CTCC used as an adjunctive agent to chemotherapy for NSCLC can improve the clinical efficacy and quality of life and decrease the likelihood of adverse reactions, suggesting that CTCC might be an effective and safe adjunctive medicine to chemotherapy for NSCLC. However, considering the relatively small sample size and the inherent imperfections of the included randomized controlled trials, more high-quality clinical trials with longer follow-up time are needed to further assess the efficacy and safety of this combined treatment regimen.